(untitled) (Journal of Mechanical Engineering, 2013)
In todays world with the increasing population, the world’s energy needs are growing steadily andthe crisis for power is also increasing. All the conventional sources of energy like gas, coal, oil etc are limited.In this situation, the need for establishing a renewable energy source as an alternative energy generation systemhas become very important for sustainable energy security of the country. Among various renewable energysources, solar energy comprises a large portion. The solar energy captivated by Earths atmosphere, oceansand land is about 385000 EJ[1]. But only less than 1% of useful energy comes from solar power [2]. Thisstatistics shows that, the sun shine produces 35000 times more power on earth than the daily power productionusing solar energy. Thus the earth receives more energy from the sun in just one hour than the world uses in awhole year.[3] The conversion of sunlight into electricity using solar cells system (10-14%) is worthwhile way ofproducing this alternative energy. Bangladesh receives strong sunshine throughout the whole year (3.8-6.42Kw-hr/m2) and it has been found that the average sunshine hours are 6.69, 6.16 and 4.81in winter, summer andmonsoon, respectively.[4] Bangladesh is also adopting means to use solar energy day by day. Many privateCompanies in Bangladesh import solar panels from abroad and sell them into the country. The approximatecost for importing readymade panels varies from 90-98 BDT per Wp. There are some companies which importsolar cells from foreign countries and assemble them into panels. The average cost for importing cells isapproximately 41-57 BDT per Wp. The cost of assembled panels from imported cells is approximately 78-84BDT per Wp. From the analysis it is found that, the cost of a locally produced PV panel is 10 percent lower thanimported ones [5] because of 60% cost incurs for producing cells from raw materials. Although solar panels arebeing produced in Bangladesh, till now solar cells have not been fabricated yet. In Bangladesh for the first timeBangladesh Atomic Energy Commission (BAEC) is going to set up a laboratory to fabricate crystalline solarcells. It is anticipated that producing cells from raw materials locally and then assembling them into PV panelswill reduce the cost almost 30%. This paper explores how fabricating crystalline solar cells locally isanticipated to reduce cost of solar panels. If the cost effective technology could be made familiar in Bangladeshthen it would help in solving our power crisis in a great deal. DOI: http://dx.doi.org/10.3329/jme.v42i1.15934